Signs through Songs: A Semiotic Analysis of Self-Confidence Lyrics - Denisa Cevania; Diah Merrita (Fakultas Sosial dan Humaniora - Universitas Buddhi Dharma, 2023)
This study investigates denotative and connotative meanings in the lyrics of three songs using Barthes’ notion of semiotics. It is conducted in order to find out the meaning of self-confidence within them by unpacking the messages appeared. This study employs descriptive qualitative research. The result reveals that all three songs contain self-confidence meanings through the denotative and connotative meanings within the song lyrics in each stanza. The lyrics implied that listeners should be able to build their self-confidence in order to face the challenges ahead and support others so that they can live peacefully without having no conflict with others.